Validation of the 2020 AHA/ACC Risk Stratification for Sudden Cardiac Death in Chinese Patients With Hypertrophic Cardiomyopathy - Dong, Yan; Yang, Wen; Chen, Chongchong; Ji, Jiamei; Zheng, Wei; Zhang, Fengxiang; Yang, Bing; Li, Xiaorong; Zhou, Xiujuan (Frontiers in Cardiovascular Medicine, 2021)
Background Sudden cardiac death (SCD) is a common cause of death in hypertrophic cardiomyopathy (HCM), but identification of patients at a high risk of SCD is challenging. The study aimed to validate the three SCD risk stratifications recommended by the 2011 ACCF/AHA guideline, the 2014 ESC guideline and the 2020 AHA/ACC guideline in Chinese HCM patients. Methods The study population consisted of a consecutive cohort of 511 patients with HCM without a history of SCD event. The endpoint was a composite of SCD or an equivalent event (appropriate implantable cardioverter defibrillator therapy or successful resuscitation after cardiac arrest). Results During a follow-up of 4.7±1.7 years, 15 patients (2.9%) reached the SCD endpoint and 12 (2.3%) was protected by implantable cardioverter defibrillator for primary prevention. A total of 13 (2.8%) patients experiencing SCD events were misclassified as low-risk patients by the 2011 ACCF/AHA guideline, 12 (2.3%) by the 2014 ESC model, and 7 (1.6%) by the 2020 AHA/ACC guideline. The SCD risk stratification in the 2020 AHA/ACC guideline showed greater area under the curve (0.71; 95% CI 0.56 to 0.87, P<0001) than the one in the 2011 ACCF/AHA guideline (0.52; 95% CI, 0.37-0.67, P=0.76) and 2014 ESC guideline (0.68; 95% CI 0.54 to 0.81, P=0.02). Conclusion The SCD risk stratification recommended by the 2020 AHA/ACC guideline showed a better discrimination than previous stratifications in Chinese patients with HCM. A larger multicenter, independent and prospective study with long-term follow-up would be warranted to validate our result.